2004
DOI: 10.1590/s1413-85572004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de leitura e desempenho em escrita no início da alfabetização

Abstract: ResumoO objetivo desse estudo foi identificar as estratégias de leitura utilizadas -logográfica, fonológica ou lexical -e a relação destas estratégias com o desempenho em escrita. Foram avaliados 55 alunos de 1ª série do ensino fundamental de escolas públicas com a Prova de Escrita sob Ditado e o Teste de Competência de Leitura Silenciosa -TeCoLeSi. Houve correlação positiva significativa entre o desempenho na Prova de Escrita sob Ditado e o TeCoLeSi (r = 0,33; p = 0,028). Os grupos de bons e maus leitores, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
25

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
0
5
0
25
Order By: Relevance
“…In addition, the results also point to the fact that with increasing ranking, the students reduced the average errors in writing with based on the semiology of the error. This is because the children make "errors" of writing appropriation during learning until, gradually, they dominate more safely orthographic system 8,20,21 . However, this study found that the students of 3 rd and 4 th year showed a similar level of orthographic knowledge and close as the rules of the Portuguese of Brazil, and higher level of orthographic knowledge compared with students of the 2 nd year, showing that from the 3 rd school year may have been a greater emphasis on spelling instruction on the rule and use, making this performance profile occur in the comparison groups.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results also point to the fact that with increasing ranking, the students reduced the average errors in writing with based on the semiology of the error. This is because the children make "errors" of writing appropriation during learning until, gradually, they dominate more safely orthographic system 8,20,21 . However, this study found that the students of 3 rd and 4 th year showed a similar level of orthographic knowledge and close as the rules of the Portuguese of Brazil, and higher level of orthographic knowledge compared with students of the 2 nd year, showing that from the 3 rd school year may have been a greater emphasis on spelling instruction on the rule and use, making this performance profile occur in the comparison groups.…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, the results appoint to the fact that with the advancement of grading, the students showed less number of writing mistakes with base in error's semiology. This is due to children committing writing appropriation "errors" during the apprenticeship until, progressively, dominate the spelling system in a securer way (2,8,18) . one (9) .…”
Section: Discussionmentioning
confidence: 99%
“…A existência de aspectos fonológicos e ortográfi -cos determinando a escrita das palavras pode levar a diversos tipos de erros os quais também podem ter frequências distintas de ocorrência. Esta incidên-cia variável reforça a hipótese de que a presença destes desvios pode ser infl uenciada por características intrínsecas da própria linguagem escrita, as quais demandam diferentes habilidades ou conhecimentos por parte do aprendiz 6,12,[18][19][20][21][23][24][25][26][27] . Na ortografi a do inglês, por exemplo, fatores como frequência e comprimento das palavras, assim como os modos de combinação das letras têm sido apontados como aspectos associados às difi culdades na soletração e na leitura, ao ponto de levar autores ao questionamento se não seria o inglês escrito, em si, uma língua disléxica 24 .…”
Section: Descritoresunclassified